2018
DOI: 10.1245/s10434-018-6461-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Predictors of Preoperative Venous Thromboembolism in Asymptomatic Patients Undergoing Major Oncologic Surgery

Abstract: Asymptomatic patients undergoing major oncologic surgery have a 10.1% prevalence of preoperative DVT. Increasing age, recent diagnosis of sepsis, and a history of prior VTE are significantly associated with preoperative DVTs. This suggests high-risk oncologic patients may benefit from screening lower extremity venous duplex ultrasound prior to Surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
3
9
0
Order By: Relevance
“…Venous thromboembolism (VTE) is a frequent complication of cancer and is the second most common reason for death among patients with cancer 1,2 . When compared to the general population, patients with cancer show a seven times higher prevalence of thromboembolism 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Venous thromboembolism (VTE) is a frequent complication of cancer and is the second most common reason for death among patients with cancer 1,2 . When compared to the general population, patients with cancer show a seven times higher prevalence of thromboembolism 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Venous thromboembolism (VTE) is a frequent complication of cancer and is the second most common reason for death among patients with cancer. 1,2 When compared to the general population, patients with cancer show a seven times higher prevalence of thromboembolism. 3 In pooled analyses of patients with varying types of cancer, those with tumors originating in the pancreas, stomach, brain, kidney, uterus, lung, and ovary had the highest incidence of VTE.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted in Japan indicated that lower limb echo screening identified soleal venous thrombosis in 8.5% of patients before general abdominal surgeries, including those for benign diseases 13. Gainsbury et al recently reported that 10% of patients undergoing major oncologic surgery had evidence of VTE preoperatively,14 suggesting that the presence of preoperative VTE in cancer patients is much higher than previously thought. In the present study, we identified DVT in 19.2% of patients awaiting colorectal cancer surgery.…”
Section: Discussionmentioning
confidence: 94%
“…According to evidence, DVT was involved in 30% patients encountered to various interventions of abdominal and thoracic surgery. The data of postoperative DVT frequency is quite controversial (4,5). If based only on clinical data it seems insignificant.…”
Section: Introductionmentioning
confidence: 99%
“…This circumstance states the extremely high percentage of lifetime undiagnosed massive embolic complications. (3,4). We analyzed in this study superiority of combined approach of thromboprophylaxis compared to conventional nonpharmacological preventive sets.…”
Section: Introductionmentioning
confidence: 99%